Some Exact Solutions of Caudrey-Dodd-Gibbon (CDG) Equation and Dodd-Bullough-Mikhailov Equation - İç, Ünal (My University, 2019)
Nonlinear partial differential equations have an important place in applied mathematics and physics. Manyanalytical methods have been found in literature. Using these methods, partial differential equations aretransformed into ordinary differential equations. These nonlinear partial differential equations are solved with thehelp of ordinary differential equations. In this paper, we implemented an improved tanh function Method for someexact solutions of Caudrey-Dodd-Gibbon (CDG) Equation and Dodd-Bullough-Mikhailov Equation.
Keywords: Matematik